Effect of Molecular Sizes of Chondroitin Sulfate on Interaction with L-Selectin. (8th May 2013) - Igarashi, Naoko; Takeguchi, Atsuko; Sakai, Shinobu; Akiyama, Hiroshi; Higashi, Kyohei; Toida, Toshihiko
Abstract : Chondroitin sulfate (CS) is a glycosaminoglycan (GAG) side chain of proteoglycans (PGs) which are widely distributed in the extracellular matrix and at cell surface. CS shows a highly structural diversity in not only molecular weight (MW) but sulfonation pattern. CS has been reported to exert anti-inflammatory activity by having effects on cytokine production by helper T cells. In this study, we focused on the structures of CS chains, especially MW of CS, and investigated effect of the different MW of CS on binding affinity with L-selectin and cytokine production by murine splenocytes. Firstly, we fractionated CS by employing gel 　 filtration chromatography and obtained several CS fractions with different MW. Then the interaction between fractionated CS and L-selectin was analyzed by surface plasmon resonance (SPR). Finally, the influence of MW of CS on cytokine production by murine splenocytes was investigated in vitro . The results showed that interferon-gamma production was significantly increased by mouse splenocytes cocultivated with CS. On the contrary, CS inhibited interleukin 5 production by murine splenocytes depending on MW of the cocultivated CS. These results strongly indicate the existence of the optimal molecular size for an anti-inflammatory effect of CS through cytokine production by murine splenocytes.